Characterization of circadian COPD symptoms by phenotype: Methodology of the STORICO observational study - Canonica, G.W.; Blasi, F.; Scichilone, N.; Simoni, L.; Zullo, A.; Giovannetti, C.; Briguglio, C.; Barsanti, S.; Antonelli Incalzi, R. (European journal of internal medicine, 2017)
Chronic obstructive pulmonary disease (COPD) is one of the leading causes of morbidity and mortality worldwide. The symptoms of COPD are troublesome, variable, can occur during all parts of the 24-h day and have a substantial impact on patients' health status, quality of life and healthcare resource utilization. Reducing symptoms, improving health status and increasing physical activity are major goals in the management of stable COPD. In order to provide effective, patient-oriented care, patients should be evaluated on the basis of lung function, frequency of symptoms and patient-perceived impact of symptoms on their lives and treatment decisions made on a case-by-case basis. The identification of COPD phenotypes is an evolving debate and literature data about the circadian variation of COPD symptoms according to phenotypes are nowadays lacking. The ongoing STORICO (STudio Osservazionale sulla caratteRizzazione dei sIntomi delle 24 ore nei pazienti con BPCO) study (NCT03105999) is aimed to describe by clinically defined phenotypes the frequency and 12-month evolution of early-morning, day- and night-time COPD symptoms in a cohort of 600 Italian patients with stable COPD. Secondary objectives include the description of the 12-month variation of outcomes of interest according to phenotypes and of the healthcare resources utilization (overall and by phenotype) during 12-month observation. An exploratory analysis will be conducted aimed to phenotype COPD patients in an alternative researcher-independent way based on circadian pattern of symptoms combined with measures of respiratory function, health-related quality of life and comorbidity. The present paper describes the methodology of the STORICO study. •COPD symptoms are troublesome and can occur during all parts of the 24-h day.•COPD symptoms impact on patients' health status, QoL and healthcare resource use.•Data on COPD symptoms' circadian variation according to phenotypes are lacking.•STORICO study will describe the evolution of COPD symptoms by clinical phenotypes.•STORICO study will investigate COPD symptoms' circadian variations by phenotypes.